Electrical performance of polymer-type insulators under various service and lightning voltage conditions - Abd Rahman, Muhammad Syahmi (2016)
Nowadays, the usage of polymer insulators are increasingly popular in the power systems and their outdoor application has resulted in the exposure to the various service conditions such as weather, pollution and lightning conditions. This study expanded previous researches by considering on the effects of wetting and pollution, i.e. clean-fog and salt-fog on the breakdown strength, voltage, electric field intensity and current density performance of a 10 kV polymer insulator under lightning impulse voltage. A set of experimental (based on IEC 60507) and simulation works revealed that the breakdown strength of insulator has significantly reduced under wet and pollution conditions where 21.18% and 53.33% of reduction was recorded, respectively due to the increase of surface conduction. Besides, the effect of insulator inclination under wetting and different pollution conditions were considered through both lab measurements and finite element modelling. The results indicated that the performance of insulator reduced up to 18.33% and the changes of electric field intensity around the insulator has been one of the factors. It should be mentioned that the inclination of insulator is one of the major problems in the electrical utilities due to line mechanical forces and the deficiency of the equipment itself. The reduction factor of U50 which is obtained from the study can be useful during the planning stage of the distribution line. The effect of lightning induced voltage on the electrical performance of polymer insulator was studied in this thesis, as it is one of the major factors for interruption of distribution lines in Malaysia. Note that the lightning induced voltage is due to the coupling between lightning electromagnetic fields and line condutors. The behaviours of electric field and voltage distribution in different parts of the insulator under lightning induced voltage condition were considered where the effects of pollution thickness, different pollution profile and humidity were investigated. It is expressed that the thickening of surface pollution can significantly increase the electric field intensity and current density for at most 62.17%. This study also found that the electric field increases due to the formation of the dry-band. Meanwhile, the increase in air humidity has been responsible to increase current density stress on the insulator surface.